Effectiveness of create sensitivity model on glycemic control and quality of life among patients with type 2 diabetes - Dini Rudini; Yulia Indah Permata Sari; Putri Irwanti Sari; Yosi Oktarina (Jurnal Keperawatan Padjadjaran, 2025)
Background: Type 2 diabetes significantly affects patients' quality of life (QOL). The "Create Sensitivity" model, integrating cognitive restructuring, patient discharge planning, self-care, and hope cultivation, offers a holistic approach to address these patients' psychological and emotional challenges. Purpose: This quasi-experimental study aimed to evaluate the effectiveness of the "Create Sensitivity" treatment model in improving glycemic control and quality of life in patients with type 2 diabetes compared to standard care. Methods: Seventy adults with type 2 diabetes were randomly assigned to either the "Create Sensitivity" intervention group (n=35) or a standard care control group (n=35). The intervention consisted of 12 weekly 2-hour group sessions. HbA1c levels, mean blood glucose, and QOL scores were measured at baseline and 12 weeks post-intervention. Data were analyzed using ANOVA with a significance level of p<0.05. Results: The "Create Sensitivity" intervention group showed significant improvements in HbA1c levels (8.7% to 5.88% vs. 8.03% to 7.71%, p<0.001), mean blood glucose levels (203.25 mg/dL to 122.12 mg/dL vs. 184.05 mg/dL to 175.02 mg/dL, p<0.001), and quality of life scores (31.63 to 58.54 vs. 37.14 to 39.8, p<0.001) compared to the control group receiving standard care, with large effect sizes for all outcomes. Conclusions: The "Create Sensitivity" program effectively improved glycemic control and QOL in patients with type 2 diabetes. Integrating psychological and behavioural strategies into diabetes management may enhance patient outcomes. Further research is needed to assess long-term impacts and broader applicability.